Produção de hidrolisado enzimático de farinha de batata-doce para fermentação etanólica - Eburneo, Juliana Aparecida Marques [UNESP] (2009)
Recently there is a great quest of producing alcohol from starchy resources, replacing the sugar cane. The most common starchy sources are cassava, maize and sweet potatoes and a lot of research are been realized with excellent results. In this work it was evaluated the influence of the concentration of dry matter on the enzymatic hydrolysis process of starch from sweet potato for ethanol production. Through the sweet potato was produced a flour using a low-cost method and easy operation equipments. The sweet potato flour was characterized physical and chemically and from these results was prepared the treatments for enzymatic hydrolysis. The experimental design considered as independent variable the dry matter concentration of the sweet potato flour in 3 levels; 10, 15 and 20% in the formulation of suspensions. The other variables were keeping constant being: temperature in the 1° hydrolysis step of 90°C and time of 2 hours; temperature in the 2° saccharification step of 60°C and time of 17 hours. The hydrolysates obtained at the three assays were transferred to six liter enlerynmeyer and inoculated with a biologic catalyst, Saccharomyces, dehydrated yeasts of Saccharomyces cerevisiae CAT 1, at a rate of 5% in weight. The flasks were placed in a shaker type orbital with controlled temperature of 30°C during a time of 15 hours. The initial reducer sugars concentration and respective ethanol concentrations in wine were: 11.2% glucose and 2.16% ethanol in the suspension with 10% of dry matter; 13.5% glucose and 4.39% ethanol with 15% and 17.5% glucose and 6.03% ethanol in suspension with 20% of dry matter. ix The results showed that the higher percentage of dry matter carried out to higher sugar yield in hydrolyzed. It was possible observed that products quality improved with a higher concentration of dry matter